2001
DOI: 10.1128/jcm.39.5.1938-1940.2001
|View full text |Cite
|
Sign up to set email alerts
|

Myxobolus sp., Another Opportunistic Parasite in Immunosuppressed Patients?

Abstract: During a study of intestinal parasitic infections in human immunodeficiency virus-positive patients, a parasite belonging to the phylum Myxozoa, recently described from human samples, was identified in one sample. When this parasite was stained by the modified Ziehl-Neelsen staining method, the features of the spores were identified: they were pyriform in shape, had thick walls, and had one suture and two polar capsules, with each one having four or five coils. The suture and two polar capsules were observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Mature spores stain weakly with hematoxylin and eosin, but are strongly acid-fast (Gardiner et al 1998). Myxozoan fish parasites have been found in human fecal samples (McClelland et al 1997, Boreham et al 1998, Moncada et al 2001. Moncada et al (2001) reported spores belonging to the genus Myxobolus based on morphology visible by light microscopy, but only in specimens stained by acidfast techniques.…”
Section: Discussionmentioning
confidence: 97%
“…Mature spores stain weakly with hematoxylin and eosin, but are strongly acid-fast (Gardiner et al 1998). Myxozoan fish parasites have been found in human fecal samples (McClelland et al 1997, Boreham et al 1998, Moncada et al 2001. Moncada et al (2001) reported spores belonging to the genus Myxobolus based on morphology visible by light microscopy, but only in specimens stained by acidfast techniques.…”
Section: Discussionmentioning
confidence: 97%
“…Developmental stages and unassigned spores were surprisingly found in inflammatory lesions of hepatic ducts in ducks (Lowenstine et al 2002). There have been also repeated findings of Myxobolus spores in the faeces of humans suffering from intestinal disorders or infected with the HIV virus (e.g., Boreham et al 1998, Moncada et al 2001, Hessen and Zamzame 2004. These reports led Canning and Okamura (2004) to postulate that myxozoans may under certain conditions become opportunistic parasites of homeothermic vertebrates.…”
Section: Hostsmentioning
confidence: 99%
“…In stool samples of humans examined for gastrointestinal disorders, spores of the genera Myxobolus Bütschli, 1822 and Henneguya Thélohan, 1892 were found and it was presumed that they were parasites of consumed fish (McClelland et al 1997, Boreham et al 1998. In another case (Moncada et al 2001), it was speculated that the Myxobolus spores found in the stool might have been the result of an opportunistic infection of an HIVinfected patient.…”
mentioning
confidence: 99%